ENHANCEMENT OF KNOWLEDGE QUALITY OF NATURAL SCIENCE STUDENTS IN MI IKHSANIAH KUPU : INTRODUCTION AND PRACTICE OF USING MICROSCOPES - Masrikhiyah, Rifatul (STKIP Santu Paulus Ruteng, 2019)
One indicator of teaching and learning is that students and students are able to explain again or be able to apply what they get during the teaching and learning process. The use of teaching aids or practices in the teaching and learning process is one way to attract students' attention in the learning process and minimize student saturation in the monotonous learning process and that's it. The purpose of this service is to improve the quality of students' knowledge about Natural Science in the Ikhsaniyah Butterfly MI. This research was in the form of community service carried out at MI Ikhsaniyah Kupu in February 2018. The target or target in this community service was elementary school-aged children who attended school in Ikhsaniyah Kupu. The subject of this community service is students of the Ikhsaniyah Kupu MI class 5 and 6. The method used uses the pre and post method. The results of this study, there is an increase in the quality of students' knowledge about Natural Science in Ikhsaniyah Kupu MI, especially regarding microscopes both benefits, functions and parts of the microscope itself which initially only about 20% of students who understood the microscope after the activity increased to 90% of the total grade 5 and 6 students